COPmax and Optimal Control of the Heat Pump Heating System Depending on the Warm Water Temperature - Arpad Nyers; Jozsef Nyers (Energies, 2025)
The primary objective is to create a control function that ensures the energetic optimization of a heat pump heating system at any point within the On-Off regulation range. The COPmax value, the optimal performance of the circulation pump, and the actual performance of the compressor are determined based on the water temperature. The objective function is the extended COP equation of the system. The COP equation includes the efficiency of the circulation pump and the compressor. With efficiency considered, the COP is 3.057; without efficiency, it is 3.68. At discrete operating points, steady-state operation is assumed; therefore, the behavior of the components is described using algebraic equations. The equation system was solved in two cycles using numerical iterative Newton linearization and Gaussian elimination methods. First, the mass flow rate was optimized for a water temperature value, then the optimization cycle was repeated at a higher temperature. The temperature increase was 2 °C. Using the values of the optimal performance of the circulation pump and the water temperature, a polynomial control function was developed. Applying the control function, the optimal performance of the circulation pump can be calculated for any operating temperature range.